The Application of Skimming and Scanning Technique to Strengthen the Understanding of Sports Management Material of Physical Education Students - Muhammad Imam Rahmatullah; Dinan Mitsalina; Endang Murti Sulistyowati; Sri Ayu Wahyuti; Elsya Desviyanti (UNIB Press, 2021)
This study aims to improve the technical ability of students in reading references related to learning process. The basis of this research is based on case studies and role play. The technique used in this research is skimming and scanning techniques. The course taken in this study is subject that researchers are capable of in learning process, namely sports management. Based on the process, this research is categorized using quantitative and qualitative approaches to strengthen research data. The subject used in this study is 30 students of the Physical Education Health and Recreation Study Program, Faculty of Teacher Training and Education, the University of Riau. In accumulating the data, the researchers took all the data by means of observation and questionnaire. The quantitative data obtained in this study were analyzed by using software with the results in the form of percentages, maximum scores, and averages. While the qualitative data in this study were analyzed by making a narration, describing the data that were taken and then concluding the final results of the study. It can be concluded that there is a significant difference in student's satisfaction before and after the treatment of skimming and scanning techniques in sport management course . The satisfaction obtained from the skimming and scanning techniques can trigger self-motivation from students to continue reading from various references and can affect the emergence of student's interest in writing.